Living in history and living by the cultural life script: How older Germans date their autobiographical memories. Issue 4 (20th April 2016) - Bohn, Annette; Habermas, Tilmann
Abstract : This study examines predictions from two theories on the organisation of autobiographical memory: Cultural Life Script Theory which conceptualises the organisation of autobiographical memory by cultural schemata, and Transition Theory which proposes that people organise their memories in relation to personal events that changed the fabric of their daily lives, or in relation to negative collective public transitions, called the Living-in-History effect. Predictions from both theories were tested in forty-eight-old Germans from Berlin and Northern Germany. We tested whether the Living-in-History effect exists for both negative (the Second World War) and positive (Fall of Berlin Wall) collectively experienced events, and whether cultural life script events serve as a prominent strategy to date personal memories. Results showed a powerful, long-lasting Living-in History effect for the negative, but not the positive event. Berlin participants dated 26% of their memories in relation to the Second World War. Supporting cultural life script theory, life script events were frequently used to date personal memories. This provides evidence that people use a combination of culturally transmitted knowledge and knowledge based on personal experience to navigate through their autobiographical memories, and that experiencing war has a lasting impact on the organisation of autobiographical memories across the life span.